Condom Use and Its Consistency among Metropolitan High School Students in Croatia, 1997– 2001: Has Anything Changed? - Hiršl-Hećej, Vlasta; Štulhofer, Aleksandar (2006)
Sexually active adolescents face serious health risks associated with unprotected sexual intercourse, such as HIV infection and other sexually transmitted diseases (STDs), as well as unwanted pregnancy. To assess protective behavior among urban adolescents in Croatia we surveyed over 4000 high-school students, 15– 19 years of age, in two waves: 2070 in 1997 and 1972 in 2001. The survey was carried out in various types of secondary schools in the capital city. The analyses suggest statistically significant increase in HIV/AIDS related knowledge in the observed period. A slight but significant increase was also observed in the acceptance of condom use. Both changes were more substantial among female students. In regards to protective behavior, we found significant increase in condom use, as well as in its consistency. Still, a large proportion of students did not use condom at last sexual intercourse (40% in 2001). In addition to generational effect, number of sexual partners, sexual victimization and mother’ s education (only in the case of young women) were identified as correlates of condom use consistency. While mother’ s education had positive effect, having 4 or more partners and having survived sexual violence decreased the likelihood of consistent condom use. In conclusion, the authors discuss the relevance of systematic school-based prevention of sexual risk taking among Croatian adolescents.
ENG